MODULATION OF BIOCHEMICAL AND ANTIOXIDANT ENZYMES IN BLOOD BY TINOSPORA CORDIFOLIA AGAINST GAMMA RADIATION MEDIATED DAMAGE IN MICE - Sharma, Priyanka; Goyal, Pradeep K (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The present investigation has been carried out to evaluate the possible radio- protective potential of root extract of Tinospora cordifolia (TCE) against 2.5 Gy gamma radiations in adult Swiss albino mice. Methods: For this purpose, healthy Swiss albino male mice were selected from an inbred colony and divided into four groups. Group I (normal) was administered double distilled water (DDW) volume equal to TCE (75 mg/kg body weight [b.wt]/animal) by oral gavage. Group II was orally supplemented TCE as 75 mg/kg b.wt once daily for 5 consecutive days. Group III (irradiated control) received DDW orally equivalent to TCE for 5 days then exposed to 2.5 Gy gamma radiation. Group IV (experimental) was administered TCE as in Group II and exposed to radiation (as in Group III) at various post-irradiation intervals between 12 hrs and 30 days. Biochemical alterations were observed in the blood of mice at various post-irradiation intervals between 12 hrs and 30 days. Results: The irradiation of mice caused considerable decrease in the level of total proteins, glutathione, catalase, and superoxide dismutase activity along with significant increase in cholesterol, lipid peroxidation (LPO). Whereas, administration of TCE prior to irradiation enhanced the activity of various antioxidant enzymes and reduced the radiation- induced variations in total proteins, cholesterol and LPO levels in the blood serum. Conclusions: Hence, the data of present investigation indicate that T. cordifolia root extract reduce the bioeffects of gamma radiation in mammals. Keywords: Gamma radiation, Tinospora cordifolia, Swiss albino mice, Blood, Antioxidant enzymes.